2009
DOI: 10.1016/j.enpol.2009.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Rebound and disinvestment effects in refined oil consumption and supply resulting from an increase in energy efficiency in the Scottish commercial transport sector

Abstract: In this paper we use an energy-economy-environment computable general equilibrium (CGE) model of the Scottish economy to examine the impacts of an exogenous increase in energy augmenting technological progress in the domestic commercial Transport sector on the supply and use of energy.We focus our analysis on Scottish refined oil, as the main type of energy input used in commercial transport activity. We find that a 5% increase in energy efficiency in the commercial Transport sector leads to rebound effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…However, in line with early results reported by Saunders (1992), Turner"s (2008Turner"s ( , 2009) analysis suggests that a key set of parameters in determining whether increased efficiency in the use of a 12 factor input reduces or increases the use of that factor is elasticities of substitution between inputs in the nested KLEM production structure in Figure 1. Therefore, in the simulations reported in Sections 4 we set the elasticity of substitution at three key nests in the multi-level production function first at a lower inelastic value of 0.4, then at a mid-point of 0.8, and finally at an elastic one of 1.1 (the 0.4-0.8 range is in line with Kemfert"s (1998) findings for the elasticities of substitution between energy/capital and labour/capital for Germany, while the fuller 0.4-1.1 range is in line with Griffin and Gregory"s (1976) findings for the UK.…”
Section: Figure One Heresupporting
confidence: 71%
See 1 more Smart Citation
“…However, in line with early results reported by Saunders (1992), Turner"s (2008Turner"s ( , 2009) analysis suggests that a key set of parameters in determining whether increased efficiency in the use of a 12 factor input reduces or increases the use of that factor is elasticities of substitution between inputs in the nested KLEM production structure in Figure 1. Therefore, in the simulations reported in Sections 4 we set the elasticity of substitution at three key nests in the multi-level production function first at a lower inelastic value of 0.4, then at a mid-point of 0.8, and finally at an elastic one of 1.1 (the 0.4-0.8 range is in line with Kemfert"s (1998) findings for the elasticities of substitution between energy/capital and labour/capital for Germany, while the fuller 0.4-1.1 range is in line with Griffin and Gregory"s (1976) findings for the UK.…”
Section: Figure One Heresupporting
confidence: 71%
“…In earlier papers (Allan et al, 2007;Anson and Turner, 2009;Hanley et al, 2006Hanley et al, , 2009Turner, 2008Turner, , 2009), we have shown that exogenous improvements in energy efficiency are likely to produce economy-wide rebound or backfire effects that partially or wholly offset energy savings from these pure efficiency improvements. This finding is consistent with a growing literature on rebound and backfire effects (see Sorrell, 2007, for a recent review).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Anson and Turner (2009) find that a 5% improvement in efficiency in energy use in the Scottish passenger and freight transportation industry has what may be considered limited impacts on key macroeconomic variables, generating long-run changes in Scottish GDP and employment of around 0.02%. However, this is accompanied by important impacts in the domestic fuel supply industry, including a shortrun decrease in revenues and return on capital that triggers what Turner terms as a disinvestment effect To halt a process of shedding capital stock/mothballing of production capacity, the local price of refined fuel which initially falls due to decreased demand from passenger and freight transporters has to rise again to restore the return on capital and achieve a new equilibrium in the sector (at a reduced level of activity) and the economy as a whole.…”
Section: Economy-wide Sectoral Level Impacts Vs Macroeconomic Effectmentioning
confidence: 99%
“…As a result, while direct rebound analyses have focussed particularly on increased efficiency in household energy use, contributors to the literature seem to draw on the limited empirical findings from studies of macro rebound effects from increased efficiency in production in widening focus to economy-wide rebound effects. However, the relatively small set of general equilibrium and non-equilibrium economy-wide studies (reviewed in Sorrell, 2007, with more recent rebound focussed case studies including Anson and Turner, 2009;Barker, 2007;Barker et al, 2009;Turner and Hanley, 2011;Wei, 2010), while putting forward some important insights on different mechanisms underlying macro-level rebound effects, have not yet established a solid theoretical foundation on the production side either.…”
Section: The Need For More Work On Theoretical Foundationsmentioning
confidence: 99%